State of the stock market of Ukraine in the system of anticrisis development - Suchkov, Artem; Brailo, Yuliia (Management and Entrepreneurship: Trends of Development, 2018)
Purpose. The paper purpose is to provide theoretical and methodological substantiation of the current state of the national stock market in Ukraine and to develop scientific and practical recommendations for the solution to the financial and economic crisis of the country.Findings. The article reflects the current state of the Ukrainian stock market during the period of the global financial crisis and the way out of it. It is known that the national stock market is at a turning point and is finding new forms and tools that could be implemented on it and additional tools to reduce the risks associated with the functioning of the market and its stable work. Today, the Ukrainian securities market is not as active as the markets of the EU and America.Research limitations/implications. The paper proves that in developed economies, the securities market is an important element of market infrastructure and the subject of state regulation. In Ukraine, it is in the stage of formation, which is characterized by the search for new tools that determine the rules of conduct of the main participants in the exchange of a specific product, such as securities. Despite the objective difficulties that arise during the formation of securities market in Ukraine, the steps taken give hope that the country will gradually approach the creation of an efficient and equitable market of government-regulated and integrated world securities marketsOriginality/value. The article is devoted to the analysis of the actual problem of identifying the features of functioning and problems of the Ukrainian stock market development, as well as substantiation of directions for increasing its liquidity and efficiency. Without a stable stock market, the functioning of a successful and developed economy is impossible.